A Study of Bilingual Acquisition of Wh-Questions of a Mandarin-English Bilingual Preschool Child from China to Australia - Qiang Guo; Ruying Qi (MDPI AG, 2024)
This article traces the developmental trajectory of a Mandarin-English bilingual child's acquisition of wh-questions from China to Australia between the ages of 3;04 and 5;05. There is an assumption that age 3 is the dividing line between Bilingual First Language Acquisition (BFLA) and Early Second Language Acquisition (ESLA). Determining the similarities and differences between them is of great theoretical and methodological significance. While BFLA studies show consistent results under conditions of adequate input and meaningful interaction, ESLA studies indicate that these children develop their early English skills differently from BFLA children. Previous studies mainly focused on young children's English development in English-speaking countries without prior English input. However, an increasing number of children migrate to English-speaking countries after age 1 with limited English input. This study examines whether there is a qualitative difference between BFLA and ESLA children's bilingual wh-questions. Drawing upon the naturalistic data before and after the child's migration from China to Australia and CLAN analysis, our 25-month longitudinal case study indicates that the ESLA child's bilingual wh-question developmental trajectories are qualitatively similar to, but quantitatively different from the child's Mandarin-English BFLA peers. This study could be the first to investigate a bilingual child who acquires two languages and experiences a change of environmental language (Lε), contributing theoretically and practically to early childhood bilingualism.